PERAN ARSITEK DALAM MERAIH TRI HITA KARANA TOURISM AWARDS PADA RANCANGAN THE ULIN VILLA & SPA DI SEMINYAK-BALI - Kadek Prana Jaya (LPPM Institut Desain dan Bisnis Bali, 2019)
Tri Hita Karana (THK) is a philosophy of life that has taken root in Hindu society in Bali. Tri Hita Karana means three causes of happiness that are created from the harmonious relationship between humans and the natural environment (Palemahan), humans and the social environment of society (pawongan), humans and the spiritual / God environment (Parhayangan). One effort to implement the Tri Hita Karana concept in the field of tourism is through annual competition and accreditation of eco-friendly tourism in the perspective of the Tri Hita Karana tourism Awards and Accreditations-THK Awards that have been held since 2000. The role of an architect in realizing Tri Hita Karana tourism Awards and Accreditations is needed especially in realizing two of the three aspects of the Tri Hita Karana tourism Awards and Accreditations, namely planning and building a villa residence. Knowledge, experience and professionalism of an architect is very much needed in translating an idea and desire of the owner and implementing oneself in the use of the environment and socio-culture of the local community, so that the design is comfortable, safe, energy efficient, economical and environmentally friendly. An architect must play a role and have a strategy to realize and apply the concepts that already exist in Bali to the fullest, so that Bali's viability can still be maintained.. Tri Hita Karana (THK) merupakan filosofi hidup yang telah berakar di masyarakat Hindu di Bali. Tri Hita Karana berarti tiga penyebab kebahagiaan yang tercipta dari hubungan harmonis antara manusia dan lingkungan alam (Palemahan), manusia dan lingkungan sosial masyarakat (pawongan), manusia dan lingkungan spiritual/Tuhan (Parhayangan). Salah satu upaya implementasi konsep Tri Hita Karana dalam bidang pariwisata adalah melalui kompetisi dan akreditasi tahunan pariwisata ramah lingkungan dalam perspektif Tri Hita Karana tourism Awards and Accreditations-THK Awards yang telah dilaksanakan sejak tahun 2000. Peran seorang arsitek dalam mewujudkan Tri Hita Karana tourism Awards and Accreditations sangat diperlukan terutama dalam mewujudkan dua dari 3 aspek Tri Hita Karana tourism Awards and Accreditations yaitu perencanaan dan pembangunan sebuah hunian villa. Pengetahuan, pengalaman dan sikap profesionalisme seorang arsitek sangat dibutuhkan didalam menterjemahkan sebuah ide dan keinginan dari owner dan mengimplementasikan diri dalam pemanfaatan lingkungan dan sosial budaya masyarakat setempat, sehingga terwujud rancangan yang nyaman,aman, hemat energi, ekonomis serta ramah lingkungan. Seorang arsitek harus berperan dan mempunyai strategi untuk mewujudkan dan menerapkan konsep-konsep yang telah ada di Bali secara maksimal, sehingga keajegan Bali masih bisa dipertahankan.